Teaching modernization : Spanish and Latin American educational reform in the Cold War - Martín García, Óscar José; Delgado Gómez-Escalonilla, Lorenzo (Berghahn Books, 2019)
"In the 1960s and 1970s, the educational systems in Spain and Latin America underwent comprehensive and ambitious reforms that took place amid a "revolution of expectations" arising from decolonization, global student protests, and the antagonism between capitalist and communist models of development. Deploying new archival research and innovative perspectives, the contributions to this volume examine the influence of transnational forces during the cultural Cold War. They shed new light on the roles played by the United States, non-state actors, international organizations and theories of modernization and human capital in educational reform efforts in the developing Hispanic world"-- Provided by publisher.
Keywords: Educational change -- Spain -- History -- 20th century.; Educational change -- Latin America -- History -- 20th century.; Education and state -- Spain -- History -- 20th century.; Education and state -- Latin America -- History -- 20th century.; Cold War -- Social aspects -- Spain.; Cold War -- Social aspects -- Latin America.; Enseignement -- Réforme -- Espagne -- Histoire -- 20e siècle.; Enseignement -- Réforme -- Amérique latine -- Histoire -- 20e siècle.; Éducation -- Politique gouvernementale -- Espagne -- Histoire -- 20e siècle.; Éducation -- Politique gouvernementale -- Amérique latine -- Histoire -- 20e siècle.; Guerre froide -- Aspect social -- Espagne.; Guerre froide -- Aspect social -- Amérique latine.; EDUCATION / Educational Policy & Reform / General; Education and state; Educational change; Social aspects; Latin America; Spain; 1900-1999; Electronic books.; History